Implementasi Global Sustainability melalui Pembuatan Ecobrick di SMKN 3 Malang - GH, Muliana; Fadli, Rahman; Permana, Tutut Indria; Hasmiati; Nomleni, Fransina Thersiana; Irawati, Mimien Henie; Rohman, Fatchur (Ininnawa : Jurnal Pengabdian Masyarakat, 2026)
The issue of plastic waste in Indonesia has become an urgent environmental concern that requires effective and sustainable management. One alternative solution that can be implemented is the use of ecobricks as a simple, practical, and educational method for managing plastic waste. This community service activity aims to improve students’ knowledge, skills, and environmental awareness through ecobrick-making training at SMKN 3 Malang. The method employed a participatory approach consisting of preparation, training and implementation, and evaluation through pre-test and post-test. This activity involved 140 tenth-grade students from the culinary department. The results showed a significant improvement in students’ knowledge, as indicated by an N-Gain score of 0.77, which falls into the high category. In addition, students were able to develop skills in making ecobricks and produce functional products such as flower pots and simple tables. This activity also contributed to enhancing students’ environmental awareness and attitudes toward plastic waste management. Therefore, ecobrick training can serve as an effective strategy to support the implementation of global sustainability and social responsibility in the school environment.